You are on page 1of 11

Module 2: Second Order Linear

ODE and Applications

Homogeneous Equations
Reading Assignment: Textbook Sections 4.1.2,4.2,4.3
If the right side function g(t) in the equation y” + p(t)y ′ + q(t)y = g(t) is
identically zero (i.e., g(t) = 0), then we call it a homogeneous second-order
linear ordinary differential equation. Otherwise it is called nonhomogeneous.

Definition 1 Principle of Superposition If y1 and y2 are two solutions of the


homogeneous equation

y” + p(t)y ′ + q(t)y = 0,

then the linear combination c1 y1 + c2 y2 is also a solution for any constants c1


and c2 .

In fact, if we substitute y = c1 y1 + c2 y2 into the homogeneous equation then



 y” + p(t)y ′ + q(t)y = (c1 y1 + c2 y2 )” + p(t)(c1 y1 + c2 y2 )′ + q(t)(c1 y1 + c2 y2 )
= c1 (y1 ” + p(t)y1′ + q(t)y1 ) + c2 (y” 2 + p(t)y2′ + q(t)y2 )

= c1 .0 + c2 .0 = 0
As corollaries, we have:
• A constant multiple y = c1 y1 (x) of a solution y1 (x) of a homogeneous
linear differential equation is also a solution
• A homogeneous linear differential equation always possesses the trivial
solution y = 0.
We need to introduce a couple of new concepts first.

Definition 2 Linear Dependence/Independence A set of non-zero functions


f1 (x) and f2 (x) is said to be Linearly dependent on an interval if there exist
constants c1 and c2 , not all zero such that

c1 f( x) + c2 f2 (x) = 0
2

for every x in the interval. If the set of functions is not linearly dependent on
the interval, then it is said to be linearly independent.

Notice that c1 = 0 and c2 = 0 will make this equation true for all x regardless of
the functions that we use.
Now, if we can find non-zero constants c1 and c2 for which the equation will
also be true for all x then we call the two functions linearly dependent. On the
other hand if the only two constants for which the equation is true are c1 = 0
and c2 = 0 then we call the functions linearly independent.
If the functions y1 (t) and y2 (t) are not proportional, i.e.,

y1 (t)
y2 (t) ̸= 0 and ̸= constant,
y2 (t)

then we say they are linearly independent.


Another criterion for linear independence is via the Wronskian. If y1 (t), and
y2 (t) are differentiable on a given interval, the Wronskian is the determinant
[ ]
y1 y2
W (y1 , y2 ) = det ′ = y1 y2′ − y1′ y2 .
y1 y2′

Fact
Given two functions f1 (x) and f2 (x) that are differentiable on some interval
I.
• If W (f1 , f2 )(x0 ) ̸= 0 for some x0 in I, then f1 (x) and f2 (x) are linearly
independent on the interval I.
• If f1 (x) and f2 (x) are linearly dependent on I then W (f1 , f2 )(x) = 0 for
all x in the interval I.
Be very careful with this fact. It DOES NOT say that if W (f1 , f2 )(x) = 0
then f1 (x) and f2 (x) are linearly dependent! In fact it is possible for two linearly
independent functions to have a zero Wronskian!
This fact is used to quickly identify linearly independent functions and func-
tions that are liable to be linearly dependent.
Before proceeding to the next topic in this section let us talk a little more
about linearly independent and linearly dependent functions. Let us start off by
assuming that f1 (x) and f2 (x) are linearly dependent. So, that means there
are non-zero constants c1 and c2 so that c1 f1 (x) + c2 f2 (x) = 0 is true for all x.
Now, we can solve this in either of the following two ways: f1 (x) = − cc12 f2 (x) or f2 (x) =
− c2 f1 (x).
c1

Note that this can be done because we know that c1 and c2 are non-zero
and hence the divisions can be done without worrying about division by zero.
So, this means that two linearly dependent functions can be written in such
a way that one is nothing more than a constant time the other. Go back and
look at both of the sets of linearly dependent functions that we wrote down and
you will see that this is true for both of them.
3

Two functions that are linearly independent cannot be written in this manner
and so we cannot get from one to the other simply by multiplying by a constant.
And we say that the y1 and y2 are linearly dependent if W (y1 , y2 ) = 0 for
all values of the independent variable t on the given interval. We say that they
are linearly independent if W (y1 , y2 ) ̸= 0 for at least one value of t on the
interval. This criterion CANNOT BE USED if one (or both) function(s) is (are)
not differentiable.
The general solution of a second-order homogeneous linear ODE is given
by the following.

Theorem 3 The general solution of the homogeneous equation

y” + p(t)y ′ + q(t)y = 0

is
y = c1 y1 + c2 y2 ,
where
1. y1 and y2 are two linearly independent solutions;
2. c1 and c2 are arbitrary constants.

We will say that two solutions y1 and y2 form a fundamental set of solutions
if every solution can be expressed as a linear combination of y1 and y2 .
Next, we do not want to leave you with the impression that linear indepen-
dence/dependence is only for two functions or second-oder ODEs. We can
easily extend the idea to as many functions as we would like. The general
solution of the n-th order homogeneous ODE

dn y dn−1 y dy
an (x) n
+ an−1 (x) n−1 + . . . + a1 (x) + a0 (x)y = 0
dx dx dx
or
dn y an−1 (x) dn−1 y a1 (x) dy a0 (x)
n
+ n−1
+ ... + + y = 0, with an (x) ̸= 0
dx an (x) dx an (x) dx an (x)
is
y = c1 y1 + c2 y2 + . . . + cn yn
where
1. y1 , y2 , . . . and yn are two linearly independent solutions, i.e.,
 
y1 y2 ... yn
 y1′
y2 ′
... yn 

 
W (y1 , y2 , . . . yn ) = det  .. .. .. ..  ̸= 0,
 . . . . 
(n−1) (n−1) (n−1)
y1 y2 ... yn
(n−1)
where yi stands for the (n−1)th derivative of the function yi (x). 2. c1 , c2 , . . .
and cn are arbitrary constants.
4

Example 4 Verify that e−t and e6t are solutions of the homogeneous equation

y” − 5y ′ − 6y = 0.

Then find the general solution of the homogeneous equation.


Solution By direct substitution we can verify that e−t and e6t are two solu-
tions.
(e−t )” − 5(e−t )′ − 6(e−t ) = e−t + 5e−t − 6e−t = 0,
(e6t )” − 5(e6t )′ − 6(e6t ) = 36e6t − 30e6t − 6e6t = 0.
Since e−t and e6t are not proportional:

e−t
= e−7t ̸= constant,
e6t
we get the general solution of the homogeneous equation

y = c1 e−t + c2 e6t ,

where c1 and c2 are arbitrary constants.

Therefore the problem of finding the general solution of a second-order ho-


mogeneous linear ODE boils down to finding two linearly independent solu-
tions. There are a number of methods for doing this. We will discuss two most
popular cases: homogeneous equations with real constant coefficients and the
method of reduction of order after we are done with the following special case.

Special Case: Euler’s Equation


For ao x2 y” + a1 xy ′ + a2 y = 0, a0 , a1 , a2 all constants, we can change variables
and use x = et , leaving us with a homogeneous linear equation with constant
coefficients bo y” + b1 y ′ + b2 y = 0. For the particular solution, we can then use
yp = xk . We could also use ax + b = et to solve ao (ax + b)2 y” + a1 (ax + b)y ′ +
a2 y = 0.

d2 y
Example 5 To solve x2 y” + 2xy ′ − 6y = 0, use x = et to get dt2 + dy
dt − 6y = 0
whose solution is

y = C1 e−3t + C2 e2t = C1 x−3 + C2 x2 .

Homogeneous Equations with Real Constant Coefficients


Now, we will see how to obtain general solutions of second-order homoge-
neous linear equations with real constant coefficients. These equations are of
the form
ay” + by ′ + cy = 0,
5

where a, b and c are real constants. According to the Linear Independence


Theorem, what we need to do is to find two linearly independent solutions of
this equation. Earlier, we found the general solution of y ′ − λy = 0 (which
corresponds to a = 0, b = 1, c = −λ) to be constant multiples of eλt . This
suggests that we try solutions of the form

y = eλt .

Substituting this exponential function into the equation, we have

(aλ2 + bλ + c)eλt = 0.

Since eλt ̸= 0, we have


aλ2 + bλ + c = 0.
The latter is called the characteristic (or auxiliary) equation for ay”+by ′ +
cy = 0,. It is indeed a quadratic equation for λ and by the quadratic formula we
know that, since a, b and c are real, the characteristic equation may only have
(Fundamental Theorem of Algebra)

• Case 1 : two real and distinct roots λ1 and λ2 (b2 − 4ac > 0),

• Case 2 : two complex conjugate roots λ1 and λ2 (b2 − 4ac < 0), or

• Case 3 : one double real root (i.e., repeated/equal real roots) λ1 = λ2


(b2 − 4ac = 0).

Hence, we conclude that

Definition 6 λ is a root of the characteristic equation → eλt is a solution of

ay” + by ′ + cy = 0.

We discuss each of the three cases listed above after we do a couple of


examples to give you a ”feel” of where we are heading with this.

Example 7 (Two distinct real roots) Find solutions of the equation

y” − y = 0.

Solution The characteristic equation is

λ2 − 1 = 0,

which has two roots λ1 = 1 and λ2 = −1. Hence, we have two linearly inde-
pendent solutions
y1 = et and y2 = e−t .
This gives the general solution y = c1 et + c2 e−t .
6

Example 8 (Two complex conjugate roots) Find solutions of the equation

y” + y = 0.

Solution The characteristic equation is

λ2 + 1 = 0,

which has two roots λ1 = i and λ2 = −i(i2 = −1). Hence, we have two linearly
independent solutions
y1 = eit and y2 = e−it .
This gives the general solution y = C1 eit + C2 e−it .
If we make use of the equality eit = cos t + i sin t, then we have

y = (C1 + C2 ) cos t + (C1 − C2 ) sin t = c1 cos t + c2 sin t

for arbitrary constants (lower-case) c1 and c2 . If you are not familiar with com-
plex exponentials, you may also directly verify that cos t and sin t are two linearly
independent solutions of y” + y = 0 using the Wronskian.

Example 9 (One double root) Find solutions of the equation

y” − 4y ′ + 4y = 0.

Solution The characteristic equation is

λ2 − 4λ + 4 = (λ − 2)2 = 0,

which has one double root λ = 2. Hence, we have only one solution y1 (t) = e2t
of exponential type.
To get the general solution, we need to find another solution not propor-
tional to e2t . Therefore, we let y2 (t) = v(t)e2t and hope v(t) is not constant.
Substituting such y2 into the equation, we have

y2 ” − 4y2′ + 4y2 = v”(t)e2t .

If y2 is a solution, then we must have v”(t) = 0, or v(t) = c1 + c2 t. Since


we do not want v(t) to be constant, it is good enough to choose v(t) = t(c1 =
0, c2 = 1) and get y2 (t) = te2t . One can check that y2 is indeed a solution. In
conclusion, we find the general solution

y = c1 e2t + c2 te2t = (c1 + c2 t)e2t .

The previous examples suggest what happens in general. We summarize


general cases as in the following table.
7

Roots of aλ2 + bλ + c = 0 General solution of ay” + by ′ + c = 0


Two distinct roots (λ1 , λ2 ) c1 eλ1 t + c2 eλ2 t

Two complex conjugate roots (α ± iβ) c1 eαt cos βt + c2 eαt sin βt

One double root (λ) (c1 + c2 t)eλt

Table 1: Table 1: General solution of ay” + by ′ + cy = 0 from roots of aλ2 + bλ +


c = 0.

Next, we explain the reasons behind the contents of Table 1.


Case 1. Two distinct real roots
In this case, we know y1 = eλ1 t and y2 = eλ2 t are solutions. Moreover, since
λ1 ̸= λ2 , we have
eλ1 t
= e(λ1 −λ2 )t ̸= constant.
eλ2 t
Therefore, y1 and y2 are linearly independent, and their linear combinations is
the general solution.
Case 2. Two complex conjugate roots
For those of you who are familiar with complex exponentials, we have a
complex general solution y(t) = C1 e(α+iβ)t + C2 e(α−iβ)t , as in the first case.
Then we may use e(α+iβ)t = eαt (cos βt + i sin βt) and e(α−iβ)t = eαt (cos βt −
i sin βt) (Euler’s formula derived from the Maclaurin series of ex ) to rewrite y
as y(t) = c1 eαt cos βt + c2 eαt sin βt, with c1 = C1 + C2 and c2 = i(C1 − C2 )
arbitrary.
Alternatively, we may directly verify y1 = eαt cos βt and y2 = eαt sin βt are
solutions. The fact that α ± iβ are complex conjugate roots means that

b 4ac − b2
α=− and β = .
2a 2a
Then


 a(y1 )” + b(y1 )′ + c(y1 ) = a(eαt cos βt)” + b(eαt cos βt)′ + c(eαt cos βt)

 = a(α2 eαt cos βt − 2αβeαt sin βt − β 2 eαt cos βt)



 +b(αeαt cos βt − βeαt sin βt) + c(eαt cos βt)

= (aα2 + bα + c − aβ 2 )eαt cos √ βt − β(2aα + b)eαt sin βt


 = [a(− 2a )2 + b(− 2a ) + c − a( 4ac−b
b b 2 2
 ) ](eαt cos βt


2a

 −β[2a(− 2a ) + b]e sin βt
b αt

= 0.eαt cos βt + 0.eαt sin βt = 0.

Similarly, we can verify that y2 is also a solution. Moreover, since

eαt sin βt
= tan βt ̸= constant,
eαt cos βt
8

we see that y1 and y2 are linearly independent. Hence, we conclude that the
linear combinations of y1 and y2 is the general solution.
Case 3. One double root
In this case, we must have b2 = 4ac and λ = − 2a b
. We already know
λt λt
y1 = e is a solution. We verify that y2 = te is also a solution as follows



 ay2 ” + by2′ + cy2 = a(λ2 teλt + 2λeλt ) + b(λteλt + eλt ) + cteλt )

= (aλ2 + bλ + c)teλt + (2aλ + b)eλt

 = 0.teλt + 0.eλt

= 0,

where the first 0 follows from the fact that λ is a root of aλ2 + bλ + c, and the
second 0 follows from λ = − 2ab
.
Since
te− 2a t
b
y2
= = t ̸= constant,
e− 2a t
b
y1
we see that y1 and y2 are linearly independent. Hence, we conclude that the
linear combinations of y1 and y2 is the general solution.

Example 10 (Two distinct real roots) Find the general solution of the differ-
ential equation
y” − 2y ′ − 3y = 0.
Solution The characteristic equation is

λ2 − 2λ − 3 = 0

with roots λ1 = 3 and λ2 = −1. Hence, we have two linearly independent


solutions y1 = e3t and y2 = e−t . The general solution is

y = c1 e3t + c2 e−t,

where c1 and c2 are two arbitrary constants.

Example 11 (Two complex conjugate roots) Find the general solution of the
dierential equation
y” + y ′ + 3y = 0.
Solution The characteristic equation is

λ2 + λ + 3 = 0
√ √
with roots λ1 = − 21 + 11
2 i, and λ2 = − 21 − 211 i. Hence, we have two linearly
√ √
independent solutions y1 = e− 2 t cos 211 t and y2 = e− 2 t sin 211 t. The general
1 1

solution is √ √
− 12 t 11 − 21 t 11
y = c1 e cos t + c2 e sin t
2 2
where c1 and c2 are two arbitrary constants.
9

Example 12 (One double root) Find the general solution of the dierential
equation
4y” + 4y ′ + y = 0.
Solution The characteristic equation is
4λ2 + 4λ + 1 = 0
with roots λ1 = λ2 = − 21 . Hence, we have two linearly independent solutions
y1 = e− 2 t and y2 = te− 2 t . The general solution is
1 1

y = c1 e− 2 t + c2 te− 2 t ,
1 1

where c1 and c2 are two arbitrary constants.


Typically, the general solution of a second-order ordinary differential equa-
tion contains two arbitrary constants. The constants can be fixed by two addi-
tional conditions. The initial conditions for y” + p(t)y ′ + q(t)y = g(t) are
y(t0 ) = y0 , y ′ (t0 ) = y1 ,
where y0 and y1 are given numbers. When these initial conditions are put
together with the ODE, we have an initial value problem.
Example 13 (Initial value problem) Solve the initial value problem
{
y” + y = 0
y( π4 ) = −1, y ′ ( π4 ) = 3.
Solution The characteristic equation is
λ2 + 1 = 0
with roots λ1 = i and λ2 = −i. Hence, we have two linearly independent real
solutions y1 = cos t and y2 = sin t. The general solution is
y = c1 cos t + c2 sin t.
The initial conditions require that
π π π
y( ) = c1 cos( ) + c2 sin( ) = −1,
4 4 4
π π π
y ′ ( ) = −c1 sin( ) + c2 cos( ) = 3,
4 4 4
which is indeed a linear system of equations for c1 and c2 . Note that cos( π4 ) =
sin( π4 ) = √12 . The linear system becomes
{
c1

2
+√ c2
2
= −1
− √12 + √
c c2
2
= 3,

which has the solution √ √


c1 = −2 2, c2 = 2.
Therefore, the solution of the initial value problem is
√ √
y = −2 2 cos t + 2 sin t
10

Method of Reduction of Order


This method deals with finding a second solution from a known solution. In
the earlier example using y” − 4y ′ + 4y = 0, the characteristic equation has
only one double root. Both roots yield the same solution y1 of the differential
equation. In order to construct the general solution, we need to find a second
solution. In fact, we applied the method of reduction of order and succeeded
in finding the second solution y2 . Note that the method can be generalized to
other equations, even equations with non-constant coefficients.
We are now going to take a brief detour and look at solutions to non-
constant coefficient, second order differential equations of the form.

y” + p(t)y ′ + q(t)y = 0.

In general, finding solutions to these kinds of differential equations can be much


more difficult than finding solutions to constant coefficient differential equations.
However, if we already know one solution to the differential equation we can
use the method that we used in the last section to find a second solution. This
method is called reduction of order.
Suppose we already have one solution y1 (t), not everywhere zero of the
second-order equation. To find the general solution, let

y2 = v(t)y1 (t),

then
y2′ = v ′ (t)y1 (t) + v(t)y1′ (t)
and
y2 ” = v”(t)y1 (t) + 2v ′ (t)y1′ (t) + v(t)y1 ”(t).
Substituting for y, y ′ and y”, we have

 0 = y2 ” + py2′ + qy2
= [v”y1 + 2v ′ y1′ + vy1 ”] + p[v ′ y1 + vy1′ ] + q[vy1 ]

= y1 v” + (2y1′ + py1 )v ′ + (y1 ” + py1′ + qy1 )v

Since y1 is a solution, we have

y1 ” + py1′ + qy1 = 0.

Thus, we have a differential equation for v:

y1 v” + (2y1′ + py1 )v ′ = 0

which is actually a first-order linear differential equation for v ′ . To see this,


denote u = v ′ , then u satisfies the first-order linear differential equation

y1 u′ + (2y1′ + py1 )u = 0
11

which can be solved by, for example, an appropriate


∫ integrating factor. Once u
has been found, then v can be obtained by v = u(t)dt + c. Finally, the general
solution can be determined from
∫ ∫ − ∫ pdt
e
y2 = vy1 = y1 [ u(t)dt + c] = y1 (t) dt.
y12 (t)

We can verify that the wronskian is (e− pdt ) not zero here. Since this process
reduces the problem of solving our second-order equation to the solution of a
first-order equation, we call it the method of reduction of order. The best way
for illustrating the method is through an example.

Example 14 Given that y1 (t) = t2 is a solution of

t2 y” − 3ty ′ + 4y = 0, t > 0,

find the general solution.


Solution Since y1 (t) = t2 is a solution of the differential equation (verify it!),
we set y = v(t)t2 . Then

y ′ = v ′ t2 + 2vt and y” = v”t2 + 4v ′ t + 2v.

The equation becomes


{ 2
t y” − 3ty ′ + 4y = t2 [v”t2 + 4v ′ t + 2v] − 3t[v ′ t2 + 2vt] + 4[vt2 ]
= t4 v” + t3 v ′ = 0

Let u = v ′ . Then we have t4 u′ + t3 u = 0, or (since t > 0)


1
u′ + u = 0.
t
The general solution of the last equation is

u = c1 t−1 ,

where c1 is an arbitrary constant. Then



v(t) = c1 t−1 dt = c1 ln t + c2 ,

where c2 is another arbitrary constant. Hence, we have the general solution

y = vy1 = c1 t2 ln t + c2 t2 ,

since t2 and t2 ln t are clearly not proportional to each other.

You might also like